Are social desirability scales desirable? A meta‐analytic test of the validity of social desirability scales in the context of prosocial behavior. Issue 2 (16th August 2021) - Lanz, Lukas; Thielmann, Isabel; Gerpott, Fabiola H.
Abstract: Social desirability (SD) scales have been used for decades in psychology and beyond. These scales are sought to measure individuals' tendencies to present themselves overly positive in self‐reports, thus allowing to control for SD biases. However, research increasingly questions the validity of SD scales, proposing that SD scales measure substantive trait characteristics rather than response bias. To provide a large‐scale empirical test of the validity of SD scales, we conducted a meta‐analysis ( k  = 41; N  = 8980) on the relation between SD scale scores and prosocial behavior in economic games (where acting in a prosocial manner is highly socially desirable). If SD scales measure what they are supposed to (namely, SD bias), they should be negatively linked to prosocial behavior; if SD scales measure socially desirable traits, they should be positively linked to prosocial behavior. Unlike both possibilities, the meta‐analytic correlation between SD scores and prosocial behavior was close to zero, suggesting that SD scales neither clearly measure bias nor substantive traits. This conclusion was also supported by moderation analyses considering differences in the implementation of games and the SD scales used. The results further question the validity of SD scales with the implication that scholars and practitioners should refrain from using them.